2009
DOI: 10.1590/s0100-39842009000500010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de meios de contraste submetidos à radiação ionizante

Abstract: OBJECTIVE: The purpose of the present study was to investigate the influence of ionizing radiation from x-rays and gamma rays on the molecular structure stability of several radiologic contrast media employed in diagnostic imaging by means of 1 H and 13 C nuclear magnetic resonance spectroscopy. MATERIALS AND METHODS: Eight different types of iodinated contrast media (three ionic and five non-ionic) were exposed to x-rays and gamma rays irradiation. Subsequently, the H} nuclear magnetic resonance spectra of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
1
Order By: Relevance
“…The use of substances to enhance the visualization of internal structures in the body through radiological images has a long history, dating back approximately half a century (PINHO et al, 2009).…”
Section: Contrast and Its Applicabilitymentioning
confidence: 99%
“…The use of substances to enhance the visualization of internal structures in the body through radiological images has a long history, dating back approximately half a century (PINHO et al, 2009).…”
Section: Contrast and Its Applicabilitymentioning
confidence: 99%
“…It is estimated that more than 80 million per year of diagnostic or therapeutic interventions using iodinated contrast media. [5][6][7] It is shown that ICM, by increasing the visibility of all surfaces of organs and tissues to be studied, may help the interventional cardiologist to determine the presence and extent of coronary artery disease or injury during the procedure of cardiac catheterization and during PCI.…”
mentioning
confidence: 99%
“…Barium Sulphate, Fluorescein, Gadolinium and iodinated contrast media (ICM) are included in the contrast media available on the market, the latter being the focus of the work. [5][6][7] The ICMs are classified according to their basic properties, which are: osmolality in relation to plasma (number of free particles), so called high-ICM(600 to 2100 mOsm/kg H2O), low osmolality (290 and 860mOsm/Kg H2O) or isosmolar (290mOsm/kg H2O) and according to their ionicity, chemical structure and viscosity. 2,4 It is reported that osmolality is the number of free particles in relation to one Kg of H2O, with the mean osmolality of the solutions and organic cells being about 290 mOsm/kg H2O, ie the closer the osmolality of the medium of iodinated contrast of the osmolality of the organic solutions, the better will be its tolerance in the human organism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No Brasil, o número de processos envolvendo doses altas de radiação tem crescido (14) e é possível observar o uso cada vez maior de radiações ionizantes para diagnóstico e tratamento médico (15). Desta forma, há a necessidade do desenvolvimento de novos dosímetros de radiação ionizante, uma vez que, até o momento, os dosímetros termoluminescentes mais utilizados no Brasil são importados, com custo elevado ou com dependência energética alta.…”
Section: Introductionunclassified